Walking a Fine Line: Physician Inquiries into Patients’ Religious and Spiritual Beliefs - Cohen, Cynthia B. (The Hastings Center report, 2001)
Modern physicians are taught that they should not involve themselves in their patients’ religious concerns. Many worry that doing so would be intrusive, manipulative, difficult, and embarrassing. Patients, however, often want their physicians to explore questions of religion and faith with them. If these questions are broached in a sensitive and flexible way, they can be a natural and appropriate part of the physician-patient relationship.